Innovative Pedagogies in Indonesian Islamic Schools: Shaping Future Leaders for a Democratic and Just Masyarakat Madani - Susanti, Sinta Ari; Murfi, Ali; Hakim, Ade Anggian; Pranata, Mohamad Waskita Adi (MyResearch ID Publishing, 2024)
Purpose – This study explores the pedagogical approaches and curricula adopted by Islamic schools in Indonesia to prepare students as future leaders of a civil society, known as